PERAN OPERATOR DALAM PELAYANAN INFORMASI TERHADAP TAMU DI HOTEL GRAND CENTRAL PEKANBARU - Chintia Lara Kharyono; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Hotel is one type of accommodation that uses part or all of the building to provide lodging, eating and drinking services and other services that are managed commercially. One of the business sectors that has been severely affected by the Covid-19 pandemic is the hotel business. Because during the corona virus outbreak, avoiding traveling or leaving the house, the increasing number of infections has made many people think twice about traveling far. Like it or not, hoteliers have to rack their brains on how to keep their business breathing in the midst of a pandemic. A hotel certainly has a department that has a big role, one of which is the Front Office Department. The operator is one of the sections in the hotel's front office. Telephone facilities at the hotel are the main key as business support. Therefore, the handling of communication systems and services in hotels is carried out by a special section known as telephone operator who must be able to uphold the hotel's image and contribute to improving the hotel's image in the eyes of guests which can be started from telephone conversations. The purpose of this study was to find out how the operator's role at Hotel Grand Central Pekanbaru. In writing this paper, the author uses qualitative data analysis techniques, namely analyzing the situation from various data collected in the form of results from interviews and observations about the problems studied that occur in the field. Keywords: Hotel, Front Office, Operator